Uma análise crítica do gênero multimodal tira em quadrinho: questões teóricas, metodológicas e pedagógicas - Predebon, Nathalia Rodrigues Catto (2012)
Recent theoretical approaches to genre have drawn attention to the need for broader analyses. On the one hand, this involves developing textual examinations that consider in detail all semiotic modes that embody these genres. On the other hand, they urge richer textual descriptions informed by contextual data collection. Proposals of this nature provide tools for a more dense discussion on the functioning of genres as mediators of social practices, socially and historically situated. In this sense, Critical Genre Analysis (MEURER, 2002, 2004; BHATIA, 2004, MOTTA-ROTH, 2005/2006, 2008b), by combining theoretical and methodological perspectives from different sources, proposes a richer research view on genre analyses, in search of more systematic connections between text and context and consistent pedagogical applications. One multimodal genre generally adopted in language teaching is the comic strip, whose recommendation is referred in official educational documents such as “Parâmetros Curriculares Nacionais” (BRAZIL, 1998a, 1998b, 1998c) and “Lições do Rio Grande” (RIO GRANDE DO SUL, 2009). Therefore, the aim of this research is directed at the analysis of the rhetorical organization of comic strips in order to provide support for more efficient reading (and production) of this genre as well as a methodological guideline for future research on multimodal genres. The corpus consists of 90 comic strips published in English selected from collections of three world-renowned characters: Calvin and Hobbes, Garfield and Mafalda. For a systematic description of the linguistic realization of the rhetorical organization of the genre, the Systemic Functional Grammar (HALLIDAY, 1994, 2004) and the Grammar of Visual Design (KRESS, van LEEUWEN, 1996, 2006) were used as tools to identify both verbal and visual patterns. The analysis revealed the functional organization of the genre into three moves: Move 1 – Contextualize, Move 2 – Generate tension, Move 3 – Present an unexpected outcome. Furthermore, three recursive elements were also observed, related to the contextual dimension of the genre: Recursive element A – Location of the comic strip in time, Recursive element B – Indication of credibility and control of the comic strip, and Recursive element C – Identification of the author of the comic strip. These moves and recursive elements show how comic strips, as indicated by their producers, aim not only at entertaining but also at criticizing social, political, economic issues in a given culture and problematize them, serving as triggers that stimulate reflective thinking. The findings reveal data that may inform the educational context more consistently when using comic strips for language teaching, particularly in relation to the promotion of multiliteracies.